1929
DOI: 10.1002/jlac.19294700110
|View full text |Cite
|
Sign up to set email alerts
|

Über die Synthese der isomeren Ephedrine und ihrer Homologen

Abstract: lm Jahre 1887 hat der eine von uns (Nagai) in der chinesischen Droge, Ma Huang, eiii neues Alkaloid, E p h ed r i n , gefunden. Nach seinen eingehenden Untersuchungen l) ist seine Konstitution so weit aufgeklart, daB es ein Abkiimmling von Propylbenzol ist , dessen Propylkette eine 08-und eine NH.CH,-Gruppe und ein o-Methyl besitzt. Seine wichtigsten experimentellen Beweise sind folgende. Ephedrin liefert einerseits durch die Oxydation mit Kaliumpermangauat (bzw. Jod) Benzaldehyd3 (bzw. Benzoesaure), Essigsaur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1930
1930
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The present study investigated the vasorelaxant effects of NPP, an intermediate in the organic synthesis of sympathomimetic drugs, such as ephedrine and norephedrine . Our findings revealed that NPP has a vasodilator profile in isolated rat aorta, with EC 50 values of around 30 μmol/L, suggesting considerable pharmacological potency for this compound.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present study investigated the vasorelaxant effects of NPP, an intermediate in the organic synthesis of sympathomimetic drugs, such as ephedrine and norephedrine . Our findings revealed that NPP has a vasodilator profile in isolated rat aorta, with EC 50 values of around 30 μmol/L, suggesting considerable pharmacological potency for this compound.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, Figure 3c shows a rightward shift of the concentrationeffect curve of NPP when the aortic rings were pretreated with 1H- [1,2,4] oxadiazolo [4,3-a]quinoxalin-1-one (ODQ; 10 μmol/L, n=6), 11 cis-N-(2phenylcyclopentyl)-azacyclotridec-1-en-2-amine hydrochloride (MDL-12330A; 3 μmol/L, n=9), 7…”
Section: Investigation Of Cell Signaling Pathways That Mediate the mentioning
confidence: 97%
See 1 more Smart Citation
“…20.4). A simple synthesis of (AE)-ephedrine and (AE)-pseudoephedrine and their subsequent resolution to the optically active varieties [9,10] are shown in Fig. 20.6.…”
Section: Synthesis Of (Ae)-ephedrine and (Ae)-ψ-ephedrine And Their Rmentioning
confidence: 99%
“…dZ-Nor-iZ'-ephedrine was synthesized from propenylbenzene via 1-phenyl-1nitroso-2-nitropropane and l-phenyl-2-nitro-l-acetoxypropane, according to the principle of Bruckner's synthesis (4); the formation of norephedrine could not be detected. The W-benzoyl derivatives of these diastereoisomers behave differently towards alcoholic hydrogen chloride; N-benzoyl-dZ-norephedrine did not undergo acyl migration in the course of three days at room temperature, whereas N-benzoyl-dZ-nor-i/'-ephedrine yielded the calculated amount of 0benzoyl-dZ-nor-i^-ephedrine hydrochloride (5). This behavior prompted us to attempt the separation of these diastereoisomers by the acyl migration reaction.…”
mentioning
confidence: 99%